Gender differences in self-reported family history of cancer: a review and secondary data analysis - Sieverding, Monika; Arbogast, Anna Lisa; Zintel, Stephanie; Wagner, Christian von (Cancer medicine, 2020)
Background Assessment of family history of cancer (FHC) mostly relies on self-report. Our goal was to find out whether there is a systematic gender difference in self-reported FHC. Methods We identified nine population-based studies which provided statistics of FHC in men and women (N1 = 404 541). Furthermore, we analyzed data (N2 = 167 154) from several iterations of the US-based Health Information National Trends Survey (HINTS) and the National Health Interview Survey (NHIS). We calculated the proportion of positive FHC, odds ratios (OR M/F), 95% confidence intervals, and aggregated statistics. We additionally analyzed in-depth questions about FHC from HINTS 5 Cycle 2. Results In the reviewed studies the odds of men reporting a FHC were lower compared with the odds of women with an average OR of 0.84 [0.71; 1.00] across all studies and an OR of 0.75 [0.70; 0.80] for the six studies from the US and Europe. The gender gap was replicated in our own analyses of HINTS and NHIS with an average OR of 0.75 [0.71; 0.79]. In HINTS 5 Cycle 2 men described themselves as less familiar with their FHC and less confident answering questions regarding FHC. They were also less likely to discuss FHC with family members. Conclusions Men— at least in the US and Europe—were consistently less likely to report FHC compared with women. Future research should investigate how the assessment of FHC can be improved to reduce these differences. Health care professionals should also consider the potential for biased reporting by gender when assessing FHC.